Transcription Factor NAC075 Delays Leaf Senescence by Deterring Reactive Oxygen Species Accumulation in Arabidopsis - Kan, Chengcheng; Zhang, Yi; Wang, Hou-Ling; Shen, Yingbai; Xia, Xinli; Guo, Hongwei; Li, Zhonghai (Frontiers in Plant Science, 2021)
Leaf senescence is a highly complex genetic process that is finely tuned by multiple layers of regulation. Among them, transcriptional regulation plays a critical role in controlling the initiation and progression of leaf senescence. Here, we found that the NAC transcription factor NAC075 functions as a novel negative regulator of leaf senescence. Loss of function of NAC075 promotes leaf senescence in an age-dependent manner, whereas constitutive overexpression of NAC075 delays senescence in Arabidopsis. Transcriptome analysis revealed that transcript levels of antioxidant enzymes such as catalase (CAT), ascorbate peroxidase (APX), and superoxide dismutase (SOD) are significantly suppressed in nac075 mutants compared with wild-type plants. Electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) analyses revealed that NAC075 directly binds the promoter of catalase 2 (CAT2). Moreover, genetic analysis showed that overexpression of CAT2 suppresses the overproduction of reactive oxygen species (ROS) and the early senescence phenotypes of nac075 mutants, suggesting that CAT2 acts downstream of NAC075 to delay leaf senescence by repressing ROS accumulation. Collectively, our findings provide a new regulatory module involving NAC075-CAT2-ROS in controlling leaf senescence in Arabidopsis.